A new clustering approach based on graph partitioning for navigation patterns mining - Jalali, Mehrdad; Mustapha, Norwati; Mamat, Ali; Sulaiman, Md. Nasir (IEEE, 2008)
We present a study of the Web based user navigation patterns mining and propose a novel approach for clustering of user navigation patterns. The approach is based on the graph partitioning for modeling user navigation patterns. For the clustering of user navigation patterns we create an undirected graph based on connectivity between each pair of Web pages and we propose novel formula for assigning weights to edges in such a graph. The experimental results represent that the approach can improve the quality of clustering for user navigation pattern in Web usage mining systems. These results can be use for predicting userpsilas next request in the huge Web sites.